Tailoring Graphene Oxide‐Based Aerogels for Efficient Solar Steam Generation under One Sun - Hu, Xiaozhen; Xu, Weichao; Zhou, Lin; Tan, Yingling; Wang, Yang; Zhu, Shining; Zhu, Jia (Advanced materials (Weinheim), 2017)
Graphene oxide‐based aerogels with carefully tailored properties are developed to enable efficient solar steam generation. Aerogels, with inherent porous structures, are excellent thermal insulators and provide channels for water supply and vapor escape. With enhanced absorption and hydrophilicity by incorporation of carbon nanotubes and sodium alginate, the resulting aerogels can enable efficient (≈83%) solar steam generation under one‐sun illumination.